2014
DOI: 10.2168/lmcs-10(1:8)2014
|View full text |Cite
|
Sign up to set email alerts
|

Separation Property for wB- and wS-regular Languages

Abstract: Abstract. In this paper we show that ωB-and ωS-regular languages satisfy the following separation-type theorem If L1, L2 are disjoint languages of ω-words both recognised by ωB-(resp. ωS)-automata then there exists an ω-regular language Lsep that contains L1, and whose complement contains L2. In particular, if a language and its complement are recognised by ωB-(resp. ωS)-automata then the language is ω-regular.The result is especially interesting because, as shown by Bojańczyk and Colcombet, ωB-regular languag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…ωT s -) regular languages. In [20], it has been shown that a language which is both ωB-and ωS-regular is also ω-regular. We aim at providing a characterization of languages which are both ωB-(resp., ωS-) and ωT -/ωT s -regular.…”
Section: Discussionmentioning
confidence: 99%
“…ωT s -) regular languages. In [20], it has been shown that a language which is both ωB-and ωS-regular is also ω-regular. We aim at providing a characterization of languages which are both ωB-(resp., ωS-) and ωT -/ωT s -regular.…”
Section: Discussionmentioning
confidence: 99%
“…A particularly interesting issue is the one about the intersections of ωB-, ωS-, and weak/strong ωB-regular languages. In [12], it has been shown that a language which is both ωB-and ωS-regular is also ω-regular.…”
Section: Discussionmentioning
confidence: 99%